2017
DOI: 10.1590/0103-8478cr20160784
|View full text |Cite
|
Sign up to set email alerts
|

Farmer field school’s training on knowledge level of citrus growers regarding improved production practices

Abstract: The major objective of this paper was to assess the impact of the Farmer field school (FFS) training program on the knowledge level of farmers (citrus growers) regarding improved citrus production practices. Distract Sargodha was the targeted research area for this study being the leading producer of citrus in Pakistan. Quantitative data were collected through interview schedule and analyzed through Statistical Package for Social Sciences (SPSS). It was conclude that young people were more tend towards getting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The negative mean difference indicates that FFS motivated the farmers in reducing fertilizer usage which is further indicated by lower means of FSS farmers compared to non-FFS farmers. Victor et al [49]; van Huis and Yajima [50] had similar findings regarding fertilizer use by FFS attending and non-attending farmers.…”
Section: Fertilizer Use Pattern Of the Farmersmentioning
confidence: 64%
“…The negative mean difference indicates that FFS motivated the farmers in reducing fertilizer usage which is further indicated by lower means of FSS farmers compared to non-FFS farmers. Victor et al [49]; van Huis and Yajima [50] had similar findings regarding fertilizer use by FFS attending and non-attending farmers.…”
Section: Fertilizer Use Pattern Of the Farmersmentioning
confidence: 64%
“…Similarly, [37] showed that FFS graduates were well equipped to apply soil management, integrated pest management, farmyard manure, and balanced fertilizer in Sargodha. [35] suggested that interactive learning and on-site training sessions vastly improved the farmer's adaptive capacity. Based on the literature review [1,34,35,44] and local context, three sustainable agriculture practices (drip irrigation, integrated pest management, and integrated soil fertility management) were selected as response variables for this study (Table 1).…”
Section: Variable Specificationmentioning
confidence: 99%
“…So far, most studies have focused on the immediate effects of FFS on IPM adoption among cotton producers [27][28][29][30][31][32][33]. However, the recent FFS project was broadly aimed at sustainable agriculture practices and facilitating sustainable livelihood among fruit producers, specifically citrus producers [3,34,35]. So far, only a few studies have discussed the effectiveness of FFS projects among citrus producers.…”
Section: Introductionmentioning
confidence: 99%
“…Agribusiness is a business activity that is engaged in agriculture that has been oriented to profit, agribusiness people consistently strive to obtain commercial and financial value on an ongoing basis to produce products that the market needs (Adjid, 1998;Antara, 2006;Muliarta, 2016;and Hermawan, 2008). Agribusiness consists of five subsystems, namely the enterprise subsystem and the procurement and distribution of agricultural production facilities, farming subsystems, product processing subsystems (agroindustry), yield marketing subsystems and supporting services subsystems (Suparta, 2005). The problems experienced so far are farming subsystems, marketing subsystems, production, and income, which are still classified as low categories.…”
Section: Development Model Of the Agribusiness System That Is Suitablmentioning
confidence: 99%
“…The problems experienced so far are farming subsystems, marketing subsystems, production, and income, which are still classified as low categories. One of the efforts that have been made by the government in making an increase in Human Resources for farmers of the chili-tobacco intercropping is through the application of field schools, which have proven to be more effective in increasing farmers 'knowledge, skills, and attitudes towards farmers and can increase farmers' production and income (Rejesus et al, 2012;Phillips et al, 2014;Victor et al, 2017). Field schools will also open up the creativity of farmers in terms of knowledge, practice, and the use and preservation of natural enemies (Palis, 2006;Guoa et al, 2015;Lampe, 2016).…”
Section: Development Model Of the Agribusiness System That Is Suitablmentioning
confidence: 99%